KEADILAN BAGI YANG BERBEDA PAHAM: REKONSILIASI DAN KEADILAN BAGI KORBAN TRAGEDI 1965 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Human rights enforcement is one improperly- accomplished agenda in this post-1998 democratisation. Severe human rights violations such as 1965 Tragedy remain obscure, nonlitigation resolution (e.g. recognition and compensation) is considered the best solution. Recognition also is a form of respect to human rights and a stepping stone to resolve other tragedies.